Proof Approach to Civil Procedures through Judge's Knowledge of Literature Review Study - Handayani, Henni Rahayu (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Proof in the legal discovery process is a very important stage. If concrete events have been proven, the judge will obtain the truth regarding the disputed event. Then, the judge will qualify the incident as a legal incident by looking for relevant legal regulations to apply. The main aim of this research is to provide a comprehensive overview of the development of research, theories and concepts in the field of literature review studies of civil procedural law evidence through the knowledge of judges by analyzing the results of empirical studies. This research uses a bibliographic method originating from reputable journals, by focusing the search through a search string through direct science, with the search focused on literature studies related to Civil Procedural Law Evidence in review articles. The results of the literature analysis in the Empirical Study include a lack of depth of discussion, a focus that is too general, not supported by relevant theory so that the theory is explained regarding legal norms governing the evidentiary process, also in the empirical study all the variables in the research are not built based on applicable theory, a lack of case analysis, a lack of in depth analysis of specific civil law cases, so it does not provide real examples of how civil law works and is not supported by research that strengthens the research results.